The Relationship between Alcohol Consumption and Cardiovascular Disease in Adults: Meta-Analysis - Moh Maulana; Shofia Andriyani (Journal of Epidemiology and Public Health, 2022)
Background: Alcoholic drink is a type of drink that contains ingredients similar to alcohol, usually ethyl alcohol or ethanol. Cardiovascular disease or also known as heart disease, generally refers to conditions that involve narrowing or blocking of blood vessels. The cardiovascular effects of alcohol consumption seen in observational studies continue to be hotly debated in the thematic literature and popular media. The purpose of this study was to analyze the relationship between alcohol consumption and cardiovascular disease in adultsSubjects and Method: This is a meta-analysis study using PRISMA flowchart guidelines and the articles were published in English from 2013 to 2022. The article search was conducted using the PICO model, Population: Adults, Intervention: Alcohol consumption. Comparison: No Consumption of alcoholic beverages. Articles obtained from the PubMed, Google Scholar and ScienceDirect databases. Based on the database, there were 9 articles that met the inclusion criteria. The analysis was carried out using Revman 5.3. software.Results: There were 9 articles from Asia, North America, and Europe, 2 articles from South Korea, 2 articles from China, 1 article from Japan, 1 article from the United States (USA), 1 article from England, 1 article from Spain and 1 article from Eastern Europe. Based on the results of the forest plot using a cohort study, it showed that someone who consumes alcohol has a high risk of cardiovascular disease by 2.83 times compared to someone who does not consume alcohol which is associated with cardiovascular disease (aHR = 2.83; CI 95% = 2.67 to 3.00; p <0.001).Conclusion: Adults who consume alcohol are at risk for cardiovascular disease. Keywords: cardiovascular, alcoholic drink, heart disease Correspondence:Moh Maulana. Medical Record Study Program, Jember Polytechnic. Jl. Mastrip, East Krajan, Sumbersari 68121, East Java. Email: maulana.rosy21@gmail.com. Mobile: +62 851-5667-1759.